Development and validation of SNP genotyping assays to identify genetic sex in the swimming crab Portunus trituberculatus - Junkai Lu (Aquaculture Reports, 2021)
The swimming crab Portunus trituberculatus is an economically vital aquaculture species in China and South East Asia. Monosex female culture has been identified as a key priority due to their increased market value, consumer preference and enhanced growth performance. However, the lack of a rapid and reliable sex-linked marker panel has hampered the application of sex control and understanding of the sex determination in the species. In this study, two sex-linked SNPs obtained from our simplified genomic data were validated by sequencing and then converted into competitive allele-specific PCR assays. The results showed high consistency between the genetic and phenotypic sex providing therefore a rapid test sex identification. Moreover, heterogametic genotypes in males provided a significant genetic evidence to support an XX/XY sex determination system in the P. trituberculatus.